Testing of a Tool for Prostate Cancer Screening Discussions in Primary Care - Misra-Hebert, Anita D.; Hom, Grant; Klein, Eric A.; Bauman, Janine M.; Gupta, Niyati; Ji, Xinge; Stephenson, Andrew J.; Jones, J. Stephen; Kattan, Michael W. (Frontiers in Oncology, 2018)
Background As prostate cancer (PCa) screening decisions often occur in outpatient primary care, a brief tool to help the PCa screening conversation in busy clinic settings is needed. Methods A previously created 9-item tool to aid PCa screening discussions was tested in 5 diverse primary care clinics. Fifteen providers were recruited to use the tool for 4 weeks and the tool was revised based upon feedback. The providers then used the tool with a convenience sample of patients during routine clinic visits. Pre- and post-visit surveys were administered to assess patients’ knowledge of the option to be screened for PCa and of specific factors to consider in the decision. McNemar’s and Stuart-Maxwell tests were used to compare pre-and post-survey responses. Results Fourteen of 15 providers completed feedback surveys and had positive responses to the tool. All 15 providers then tested the tool on 95 men age 40-69 at the 5 clinics with 2-10 patients each. The proportion of patients who strongly agreed that they had the option to choose to screen for PCa increased from 57-72% (p=0.018) from the pre- to post-survey, that there are factors in the personal or family history that may affect PCa risk from 34 to 47% (p=0.012), and that their opinions about possible side effects of treatment for PCa should be considered in the decision from 47 to 61% (p=0.009). Conclusions A brief conversation tool for the PCa screening discussion was well-received in busy primary care settings, and improved patients’ knowledge about the screening decision.